Duration of Hospitalization in Association with Type of Inhalation Therapy Used in the Management of Children with Nonsevere, Acute Bronchiolitis - Jamie M. Pinto; Janet L. Schairer; Anna Petrova (Pediatrics and Neonatology)
Acute bronchiolitis is one of the main respiratory emergencies in young children. Although supportive therapy is recommended, substantial inconsistency in the clinical usage of inhaled treatments has been reported. In the present study, we evaluated the association between different types of nebulized therapies in clinical practice and the length of stay (LOS) of young children hospitalized with nonsevere bronchiolitis. Methods: Medical records of 195 patients with bronchiolitis, without evidence of pneumonia or congenital/chronic respiratory conditions, were stratified with respect to the type of inhalation therapy received: nebulized albuterol (Group 1, n = 53), nebulized albuterol with 3% saline (Group 2, n = 38), nebulized 3% saline alone (Group 3, n = 33), or no inhaled treatment (Group 4, n = 71). Duration of hospital stay was reported with respect to the type of inhalation therapy received after controlling for variability in patient age (months), oxygen saturation, respiratory score, and use of other treatments (antibiotics, oxygen supplementation, and/or corticosteroids). LOS is presented in terms of mean and 95% confidence interval (95% CI). Results: The groups were similar except for differences in the mean level of oxygen saturation, respiratory score, and corticosteroid use. Children in Group 4 had the lowest mean respiratory score due to a lesser prevalence of wheezing and/or retractions than in other groups. The LOS for children in Groups 1 and 4 was shorter (43.2 hours, 95% CI 34.9–51.3, and 44.1 hours, 95% CI 37.3–51.0, respectively) than in Groups 2 and 3 (72 hours, 95% CI 62.1–81.6, and 65.1 hours, 95% CI 54.7–75.6, respectively) (p < 0.02). The mean LOS in each group did not change significantly after adjustment for covariants. Conclusion: Prolonged hospitalization of children younger than 2 years with acute, nonsevere bronchiolitis is associated with administration of nebulized 3% saline, independent of age, clinical presentation of disease, or inclusion of other treatments in their management.